2021
DOI: 10.3390/ijms22041613
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge of the Pathogenesis of Atopic Dermatitis: Sphingomyelin Deacylase, the Enzyme Involved in Its Ceramide Deficiency, Plays a Pivotal Role

Abstract: Atopic dermatitis (AD) is characterized clinically by severe dry skin and functionally by both a cutaneous barrier disruption and an impaired water-holding capacity in the stratum corneum (SC) even in the nonlesional skin. The combination of the disrupted barrier and water-holding functions in nonlesional skin is closely linked to the disease severity of AD, which suggests that the barrier abnormality as well as the water deficiency are elicited as a result of the induced dermatitis and subsequently trigger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 78 publications
0
17
2
Order By: Relevance
“…17 In contrast to the present study, there was no difference in GBA activity between healthy and AD skin; however, that study did not report details on disease severity, skin barrier function or sampling distance from lesional skin. 17 In another study, Boer et al reported differences in the localization, expression and activity of GBA in the epidermis between healthy and AD skin. 10 Altered localization of active GBA in AD skin was mainly detected in lesional skin, while the difference between healthy and nonlesional atopic skin was inconsistent.…”
Section: Discussioncontrasting
confidence: 98%
“…17 In contrast to the present study, there was no difference in GBA activity between healthy and AD skin; however, that study did not report details on disease severity, skin barrier function or sampling distance from lesional skin. 17 In another study, Boer et al reported differences in the localization, expression and activity of GBA in the epidermis between healthy and AD skin. 10 Altered localization of active GBA in AD skin was mainly detected in lesional skin, while the difference between healthy and nonlesional atopic skin was inconsistent.…”
Section: Discussioncontrasting
confidence: 98%
“…Furthermore, cracks in the epidermis caused by dehydration of the s. corneum increases susceptibility to bacterial and viral infections, as well as sensitization by allergens, which are risk factors for infectious diseases [37] and skin allergies [38]. Assessing the primary outcome, cheek TEWL after 4 weeks and after 12 weeks of the Oryza Ceramide ® intervention was significantly reduced (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased amounts of CERs in the SC of AD patients are not due to increased degradation via endogenous ceramidase [90,94,95]. It has been hypothesized that enrichment of the skin microbiota with ceramidase-secreting bacteria might contribute to reduced levels of CERs in the SC of both lesional and non-lesional AD skin [96].…”
Section: -Hydroxy-sphingosine Moieties (H) the Levels Of Cer [As] Cer...mentioning
confidence: 99%
“…In line with this, decreased availability of phospholipids, as evidenced in AD epidermis, might contribute to reduced amounts of CERs; however, metabolic changes leading to lower amounts of CERs in AD remain to be fully deciphered. Decreased amounts of CERs in the SC of AD patients are not due to increased dation via endogenous ceramidase [90,94,95]. It has been hypothesized that enrichm the skin microbiota with ceramidase-secreting bacteria might contribute to reduced of CERs in the SC of both lesional and non-lesional AD skin [96].…”
Section: -Hydroxy-sphingosine Moieties (H) the Levels Of Cer [As] Cer...mentioning
confidence: 99%